Effects of child marriage on girls'right to education in Masvingo District - Zimuto, Moreblessing (Midlands State University, 2020)
The purpose of this study is to explore the effects of child marriage on girl’s educational rights. The study managed to look at the factors that have contributed to child marriages. In as much, the researcher also looked at how these causes of child marriage have been an obstacle to girl’s attainment of education hence suppressing their education rights. The study also looked at the effects of child marriages on girl’s education rights; these include poor academic performance, sexual harassment, stigmatization and discrimination, violence and failure to proceed with education. The researcher used local leaders in identifying victims of child marriage in Masvingo District in the Nemamwa Community under the chieftainship of Fortune Charumbira and she managed to do fifteen interviews. The research centered on the survivors of child marriage, as the researcher believed that they could provide real lived experiences of the effects of child marriages on the girl’s education rights. The researcher used qualitative approach, as she believed that it would produce meaningful piece of scholarly work. The study however concludes by recommending the strategies that needs to be put in place to do alleviate the challenges of child marriage and to cope with the effects of child marriage on the girl’s education rights, promoting education rights among married girls.